IDENTIFIKASI PRODUK TURUNAN HYDROPROCESSING MODEL MINYAK SINTETIS BATUBARA MENGGUNAKAN GC-FID/NPD/MS - Muhammad Hanif; Yusnitati Yusnitati; Nasikin Nataadmadja (Jurnal Energi dan Lingkungan (Enerlink), 2010)
An analysis of identifying a derivative product of liquefied coal modelhydroprocessing was conducted. For that purpose, an integration gaschromatography flame ionization-nitrogen phosphorous detector and massspectrometry (GC-FID/NPD/MS) was used. Hydroprocessing process wasperformed by vibrating micro autoclave tipe batch using Ni-W/Alumina catalystunder initial hydrogen pressure 6 MPa, reaction temperature 375oC and one hourretention time. The analysis result showed that the predominant reaction werehydrogenation, hydrodenitrogenation (HDN) and hydrodeoxygenation (HDO).The HDO of methyl phenol and ethyl phenol took place faster than the otherhydroprocessing reactions such as HDN of quinoline and aromatic hydrogenation(butyl benzene, naphthalene, phenanthrene dan pyrene). This indicates that thehydrogenation reaction or the cleavage of C-O bonding took place very fast thatalkyl could not be detected in the oil. The HDN reaction or the cleavage of C-Ntook place slower but the the nitrogen containing compound vanished faster dueto selective adsorption of the catalyst. However the hydrogenation reaction ofmono-aromatic took place faster than poly-aromaticKata kunci: gas chromatography, identifikasi senyawa, model minyak sintetis